Pregnancy Exercises on Reducing Lower Back Pain In Pregnant Women Trimester II and III - Pangaribuan, Ingka Kristina; Lubis, Khairani; Yanti, Safrina; Sibarani, Lisa (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Abstract A pregnant woman is a woman who carries a pregnancy starting from conception until the birth of the fetus (Prawirohardjo, 2018). Pregnancy is the period when a woman carries an embryo or fetus in her body. The pregnancy period starts from conception until the birth of the fetus (Prawirohardjo, 2018). The general aim of this research is to determine the effect of pregnancy exercise on reducing lower back pain in pregnant women in the second and third trimesters at the UPTD of the Tanjung Balai City Natural Health Center in 2023. This research uses a quasi-experimental research design with a pre-post test design with one group test. The results of the research were 33 respondents, namely patients with lower back pain in pregnant women in the second and third trimesters at the UPTD of the Tanjung Balai City Natural Health Center in 2023, respondents only used one intervention group. The results of this research consist of univariate and bivariate analysis. Research conclusions:The majority of lower back pain for pregnant women in the second and third trimesters before doing pregnancy exercise was moderate pain as many as 33 respondents (100%), lower back pain for pregnant women in the second and third trimesters after doing pregnancy exercise, back pain for pregnant women became moderate pain for 18 people (54, 4%), 13 people (39.2%) had mild pain and 2 people (6.1%) had no pain. There was an effect of pregnancy exercise on reducing lower back pain in pregnant women in the second and third trimesters at UPTD Puskesmas Semula Jadi. Tanjung Balai City in 2023 with a value of p=0.001 p<0.05 KEYWORDS: Pregnancy exercise, pregnant women TM II and III, decreased back pain